2022
DOI: 10.1039/d2dt00321j
|View full text |Cite
|
Sign up to set email alerts
|

Mixed superalkalis are a better choice than pure superalkalis for B12N12 nanocages to design high-performance nonlinear optical materials

Abstract: Mixed superalkali clusters are source of excess electrons as their vertical ionization energies (2.81-3.36 eV) are much smaller than alkali metals (even cesium≈3.85 eV) and Li3O superalkali (3.42 eV). In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Very recently, Bano et al presented theoretical work where they showed that the mixed superalkalis (Li 2 NaO, Li 2 KO, Na 2 LiO, Na 2 KO, K 2 LiO, K 2 NaO, and LiNaKO) could be a better alternative than the pure superalkalis for B 12 N 12 nanocages in designing hi-tech NLO materials ( Bano et al, 2022 ). The optimized structures of the mixed-superalkali-doped B 12 N 12 complexes can be seen in Figure 2A .…”
Section: High-performance Nlo Response Material/molecular Switchmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Bano et al presented theoretical work where they showed that the mixed superalkalis (Li 2 NaO, Li 2 KO, Na 2 LiO, Na 2 KO, K 2 LiO, K 2 NaO, and LiNaKO) could be a better alternative than the pure superalkalis for B 12 N 12 nanocages in designing hi-tech NLO materials ( Bano et al, 2022 ). The optimized structures of the mixed-superalkali-doped B 12 N 12 complexes can be seen in Figure 2A .…”
Section: High-performance Nlo Response Material/molecular Switchmentioning
confidence: 99%
“… (A) Optimized geometries of the most stable complexes of mixed-superalkali-doped B 12 N 12 adapted from Bano et al (2022) with permission from the Royal Society of Chemistry; (B) optimized structures of C 6 Li 6 -nCO 2 complexes (front and side views) for n = 1–6 adopted from Srivastava (2019b) with the permission of Wiley. …”
Section: High-performance Nlo Response Material/molecular Switchmentioning
confidence: 99%